Developing Logic Building, Problem Solving, and Debugging Programming Skills Among Students - Thorat, Sandeep A.; Kshirsagar, Durgesh P. (Journal of Engineering Education Transformations, 2021)
Computer programming course has become integral part of first year curriculum in all engineering disciplines. The effectiveness in delivery of this Course largely impacts on student’s curiosity in the field of programming and software development. Many students lose their interest in the coding at very early stage of their professional career if this Course is not taught effectively. The proposed work aims to improve academic delivery of the computer programming course. This work identifies loopholes in existing method of teaching computer programming course. Further we attempt to address these identified problems with different approaches. The approach focuses on development of logic building, problem solving, and debugging skills among the students. It is observed that if these skills are addressed properly then realistic improvement in programming skills of students can be achieved. We observed improvements in academic results of computer programming course after implementation of the proposed method. The approach proposed here can make learning computer programming a joyful experience for the students.